Reinforced concrete beam column joints with crossed inclined bars under cyclic deformations. - Chalioris, Constantin E.
This experimental study investigates the effectiveness of crossed inclined bars (X-bars) as joint smear reinforcement in exterior reinforced concrete beam column connections under cyclic deformations. Test results of 20 joint subassemblages with various reinforcement ratios and arrangements including X-bars in the joint area are presented. The X-type, non conventional reinforcement is examined as the only joint reinforcement and in combination with common stirrups or vertical bars. The experimental results reported herein include full loading cycle curves, energy dissipation values and a categorization of the observed damage modes. Based on the comparisons between the overall hysteretic responses of the tested specimens, it is deduced that joints with X-bars exhibited enhanced cyclic performance and improved damage mode since a distinct flexural hinge was developed in the beam joint interface. Further, the combination of crossed inclined bars and stirrups in joint area resulted in enhanced hysteretic response and excellent performance capabilities of the specimens. However, in some specimens with X-bars as the only joint shear reinforcement, the deformations of the bent anchorage of the beam's bars caused considerable damages at the back of the joint area. Discussion for a potential replacement of the joint stirrups with X-type reinforcement in some cases of exterior joints is also included.
Keywords: Beam column joints; Cyclic test; Inclined bars; Reinforced concrete